Preventing Stunting by Improving Nutrition Through the Provision of Animal Protein (Eggs) - Puji Astuti; Muhammad Yusuf Ariyadi; Uswatun Hasanah; Amirulloh Moh Rumuntoha; Nandana Pangestu Muwahid (Pascasarjana Universitas Mataram, 2025)
Stunting remains a significant public health problem in Indonesia, with long-term consequences for child development and human capital quality. One of the underlying causes is the low intake of animal-source protein, which plays a crucial role in supporting children’s growth and cognitive development. This community service program aimed to prevent stunting by providing nutrition education and distributing eggs as an affordable, accessible, and nutrient-dense source of animal protein. The method applied was Participatory Action Research (PAR), consisting of stages such as socialization, nutrition education, egg distribution to families with toddlers, and monitoring of both egg consumption and parental nutrition knowledge. The results indicated an improvement in parental understanding of the importance of animal protein, an increase in the frequency of egg consumption among toddlers, and active involvement of local health cadres in nutrition monitoring. The discussion links local findings with recent evidence highlighting the role of eggs in improving child nutrition, while emphasizing that sustained interventions are needed for significant impacts on linear growth. This program contributes to the national target of stunting reduction and strengthens household nutrition resilience in the partner village.